Era Reformasi: Implementasi Negara Hukum dan Demokrasi di Indonesia - Bahari, Beno; HB, Gusliana (Legalitas: Jurnal Hukum, 2023)
The history of the Indonesian constitution can be said to have gone through various stages of development. Each stage gives rise to a unique constitutional model. After the New Order and the 1998 events, Indonesia began a new chapter in the reform era which saw several government era changes. Each government has its own characteristics in running its government. The aim of writing this article is to understand the implementation of the rule of law and democracy in reform. This research is qualitative research that is bibliographic in nature (library research) to examine the concept of the legal state as the main object in this research. The research results show that a constitutionally based rule of law in a country has characteristics that are each adapted to the nation's philosophy and legal ideals. Therefore, in a democratic rule of law, it is the people who are considered to determine the enactment of a constitution. The embodiment of democratization in Indonesia is the existence of the concept of government decentralization since the reform era as an anti-thesis to the concept of centralization implemented by the New Order. The implication is that there is a shift in the locus of power from the center to the regions. With the spirit of decentralization, regions increasingly have broader autonomous authority.Â Â